Hypofractionated Stereotactic Body Radiotherapy in Spinal Metastasis — With or Without Epidural Extension. Issue 6 (June 2015) - Anand, A.K.; Venkadamanickam, G.; Punnakal, A.U.; Walia, B.S.; Kumar, A.; Bansal, A.K.; Singh, H.M.
Abstract Aims To evaluate clinical outcome and the effect of malignant epidural compression (MEC) in the treatment of spine metastasis with stereotactic body radiotherapy (SBRT). Materials and methods Seventy-six lesions in 52 patients with spinal metastasis received SBRT during the period July 2010 to December 2012. MEC was detected in 20 patients (38.4%) and was separately contoured. The median dose prescribed to involved vertebra (planning target volume) was 24 Gy (range 24–27 Gy) in a median of three fractions (range 1–3). Uninvolved elements were prescribed 21 Gy in three fractions. In 59 lesions (77.6%), the entire vertebra was treated and in 17 lesions (22.4%) only the anterior elements were treated. All patients were treated with volumetric modulated arc therapy with image guidance on a Novalis Tx linear accelerator with the ExacTrac system. Dosimetric and clinical outcomes were compared in patients with or without MEC. Results At a median follow-up of 8.48 months (range 3–40 months), 1 year local control and overall survival was 94 and 68%, respectively. In patients with or without epidural extension, the median dose to the gross tumour volume (GTV; 95%) was 23.48 Gy (range 13.70–25.75) and 22.99 Gy (range 13.55–26.84), the median spinal cord Dmax was 17.36 Gy (range 8.47–21.63) and 15.71 Gy (range 8.39–23.33). The median GTV epidural (D95%) was 21.16 Gy (range 15.43–23.92). Complete pain relief was seen in 90% of patients with MEC and 93.75% without MEC (P = NS) and neurological improvement was seen in 60% of patients in both groups of patients. Conclusion It is feasible to deliver a high dose of radiation (∼90% of the prescription dose) to the epidural component with volumetric modulated arc therapy SBRT and image guidance. It yielded high rates of pain control and local control in patients with spine metastases with or without MEC.